Desain dan Analisis Alat Bending V Sistem Hidro Pneumatik - Muhammad Jufri Dullah; Muhammad Arsyad Suyuti; Sudarman Sudarman; Mariam Mariam; Muh Azwar Arham (Jurnal Teknik Mesin Sinergi, 2019)
The design of the pneumatic hydro system V bending tool serves as an alternative tool for bending plates replacing the manual bending method which is widely used in the industrial community, especially machining workshop workshops today. In this design the hydraulic jack bender is driven by a pneumatic cylinder so that the workload of the operator is lighter. As for the results of this design and analysis, a V bending tool with 750 mm frame height, 650 mm frame width, 150 mm hydraulic stroke length, and 5 mm diameter spring pull wire are obtained. In addition, the punch angle is 85o and the punch radius is 1.5 mm while the die angle is 85o, the width of the V die is 33 mm and the bending line capacity is 300 mm. The punch and die material chosen is steel AISI 1045.